ANALISIS KINERJA KEUANGAN DAERAH KOTA SAMARINDA - -, NUR’AINI - (EKONOMIA, 2017)
The purpose of this study is to determine the financial performance of the city of Samarinda from 2013 until 2015. Analyzer in measuring the effectiveness and efficiency of financial performance of the city of Samarinda by using effectiveness ratio, effectiveness criteria table, efficiency ratio and efficiency criteria table.The results of research conducted, it is known that the financial performance of the Local Government of Samarinda City from the period of 2013 local government finances Samarinda City is very effective because the effectiveness ratio is greater than 100%. In the period of 2014, the financial performance of Samarinda City Government was less effective because its effectiveness ratio was smaller than 90% and showed a downward trend. In the period of 2015 the regional finances of the Samarinda City Government were also less effective. This is because the effectiveness ratio is smaller than 90% and also indicates a downward trend.The financial performance of the Local Government of Samarinda City in the period of 2013 if measured by the ratio of the efficiency of local revenue (PAD) is inefficient, this is because the efficiency ratio is greater than 80%. In the period of 2014 the financial performance of Samarinda City Government is less efficient, this is because the efficiency ratio of Samarinda City Government is greater than 80% and shows an increasing trend. While in the period of 2015, the financial performance of Samarinda City Government is also less efficient. This is also caused by the ratio of efficiency of Local Original Income (PAD) is greater than 80% and shows the trend of denial.Thus it can be concluded that the hypothesis in the period of 2013 for the effectiveness ratio is rejected because the level of effectiveness is greater than 90%, the hypothesis of 2014 accepted because the level of effectiveness is smaller than 90%, while in the period 2015 hypothesis proposed is also accepted because the level of effectiveness more Small than 90%. For the efficiency level in the period of 2013 the hypothesis presented is accepted, this is because the level of efficiency is greater than 80%. In the period 2014, the hypothesis was accepted because the level of efficiency is greater than 80%. And the period of 2015, the hypothesis put forward previously accepted this is also due to the level of efficiency is also greater than 80%